Design of the dual-buoy wave energy converter based on actual wave data of East Sea - Jeongrok Kim (International Journal of Naval Architecture and Ocean Engineering, 2015)
A new conceptual dual-buoy Wave Energy Converter (WEC) for the enhancement of energy extraction efficiency is suggested. Based on actual wave data, the design process for the suggested WEC is conducted in such a way as to ensure that it is suitable in real sea. Actual wave data measured in Korea’s East Sea (position: 36.404 N° and 129.274 E°) from May 1, 2002 to March 29, 2005 were used as the input wave spectrum for the performance estimation of the dual-buoy WEC. The suggested WEC, a point absorber type, consists of two concentric floating circular cylinders (an inner and a hollow outer buoy). Multiple resonant frequencies in proposed WEC affect the Power Ttake-off (PTO) performance of the WEC. Based on the numerical results, several design strategies are proposed to further enhance the extraction efficiency, including intentional mismatching among the heave natural frequencies of dual buoys, the natural frequency of the internal fluid, and the peak frequency of the input wave spectrum.